Effect of Metoclopramide on the Incidence of Early Postoperative Aspiration Pneumonia in Dogs with Acquired Idiopathic Laryngeal Paralysis. Issue 5 (8th June 2016) - Milovancev, Milan; Townsend, Katy; Spina, Jason; Hurley, Connie; Ralphs, S. Christopher; Trumpatori, Brian; Seguin, Bernard; Jermyn, Kieri
Abstract : Objective: Evaluate the effect of a perioperative intravenous continuous rate infusion (CRI) of metoclopramide on the incidence of aspiration pneumonia in the short term postoperative period in dogs undergoing unilateral arytenoid lateralization. Study Design: Prospective, randomized, multi‐center clinical trial. Animals: 61 client‐owned dogs with idiopathic laryngeal paralysis and normal preoperative thoracic radiographs. Methods: All dogs underwent unilateral arytenoid lateralization with a uniform anesthetic, analgesic, and management protocol. Dogs in the treatment group received an intravenous CRI of metoclopramide for 24 hours perioperative. All dogs were assessed for clinical signs of aspiration pneumonia based on the results of physical examination and owner interview up to the point of suture removal (10–14 days postoperative). Any dog with suspected aspiration pneumonia had thoracic radiographs performed. Results: Six dogs developed aspiration pneumonia in the short term postoperative period (2/28 control dogs and 4/33 treated dogs), accounting for an overall frequency of 10% with no significant difference between control and treated dogs. No variables measured in the study were significantly different between control and treated dogs. Conclusions: Perioperative metoclopramide, at the doses used in this study, did not affect the incidence of aspiration pneumonia in the short term postoperative period in dogs with idiopathic laryngeal paralysis undergoing unilateral arytenoid lateralization.